Strategi Optimalisasi Pembelajaran Pendidikan Agama Islam di Era Society 5.0 - Rifatul Izza (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The rapid development of information and communication technology has brought the world into the era of society 5.0, which is an era that is human-oriented and supported by technological advances. This condition requires the world of education, including Islamic Religious Education (PAI), to adapt creatively and innovatively to remain relevant to the needs of the times. This study aims to analyze the concept and strategy of optimizing PAI learning in the era of society 5.0. The research method used is qualitative with a descriptive-argumentative approach through literature studies on various scientific sources, including books, national and international journals, and online publications. The results of the study show that PAI optimization in the 5.0 era can be achieved through four main steps, namely: (1) revitalization of the learning system by utilizing digital technology such as Zoom, Google Meet, and Discord; (2) strengthening collaboration between educational elements; (3) the integration of PAI values into general subjects to remove the dichotomy between science and religion; and (4) learning evaluation that not only assesses cognitive aspects but also affective and psychomotor aspects. PAI in the era of society 5.0 must be directed to form students who are not only intellectually intelligent, but also have strong spiritual, moral, and social characters. Thus, technology-based PAI optimization is the key to building a generation that is religious, adaptive, and competent to face global challenges.   Keywords: Islamic Religious Education, Society Era 5.0, Learning Optimization.